2019
DOI: 10.7717/peerj.6197
|View full text |Cite
|
Sign up to set email alerts
|

Carabid community structure in northern China grassland ecosystems: Effects of local habitat on species richness, species composition and functional diversity

Abstract: BackgroundMost carabid beetles are particularly sensitive to local habitat characteristics. Although in China grasslands account for more than 40% of the national land, their biodiversity is still poorly known. The aim of this paper is to identify the main environmental characteristics influencing carabid diversity in different types of grassland in northern China.MethodsWe investigated the influence of vegetation (plant biomass, cover, density, height and species richness), soil (bulk density, above ground li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 76 publications
5
31
0
Order By: Relevance
“…In a previous study, we found that climate factors influenced carabid functional diversity in different types of steppes [16]. Here, we found that climate factors were also important drivers of carabid activity density in the studied ecosystems.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In a previous study, we found that climate factors influenced carabid functional diversity in different types of steppes [16]. Here, we found that climate factors were also important drivers of carabid activity density in the studied ecosystems.…”
Section: Discussionsupporting
confidence: 65%
“…Since we detected a VIF = 10.65 for ST in the desert steppe (Table S1), this variable was no longer considered in the analyses for this ecosystem. Further details about this type of analysis can be found in a companion paper [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, climatic factors may partly explain the variation of alpha diversity (Xiao-Dong et al, 2016). Climatic predictors (temperature, precipitation, and air humidity) have positive effects on carabid species richness at regional and ecosystem levels, with differences between ecosystems (Tsafack et al, 2019). For all organisms, temperature can determine species richness through its effect on metabolic biochemical kinetics (Sanders et al, 2007).…”
Section: Nov Dec Janmentioning
confidence: 99%